Investigation of optical and electrical properties of chemically deposited nanocrystalline CdO thin fil (Journal of the College of Basic Education, 2022)
nano crystalline CdO films have been deposited by chemical bath deposition technique, where the cadmium acetate salt (Cd(CH3COO)2)used as a source of cadmium ions. The spectral transmission and the optical energy band gap increase from 84% and 2.47eV (for bulk CdO) to 95% and 2.92 eV(for nano CdO) respectively. This has been obtained as a result of quantum confinement with low values of conductivity and carriers mobility.